Sweet bread chemical properties optimalization based on baking temperature and duration - Devi Dwi Siskawardani; Warkoyo Warkoyo; Jumpen Onthong (Hasanuddin University Food Science and Technology Study Program, 2021)
Bread is main food in several country. Sweet bread is one popular type that has a lasting sweet taste and soft textured with or without stuffing. Baking is the most important process of bread production. The temperature and time required in the baking varies according to the type of bread, big dough, and baking pan in the oven used. This research aimed to identify the optimum level of baking temperature and duration to the chemical properties of sweet bread. Randomized Complete Block Design (RCBD) Factorial with 2 factors and 3 replications were applied for this research. The first factor was baking temperature consisted 4 level (T1= 180 oC, T2= 190 oC, T3= 200 oC, T4= 210 oC), and the second factor was baking duration which composed 4 level (A1= 10 minutes, A2= 15 minutes, A3= 20 minutes, A4= 25 minutes). The results showed that there wasn’t interaction between baking temperature and duration to water content, fat, protein, and carbohydrate, but it was interaction to the ash content. The baking temperature and duration separatelly had significantly effect to the all parameter. The best result according to the SNI 01-3840-1995 was S4W4 (185 oC: 14 minutes) with water content (23.572%), fat (10.906), protein (1.105%), carbohydrate (62.940 %), and ash content (1.736 %).